2021
DOI: 10.17749/2077-8333/epi.par.con.2021.083
|View full text |Cite
|
Sign up to set email alerts
|

Modern possibilities of antiepileptic therapy at the start of treatment of focal epilepsy

Abstract: The report presents data on the evaluation of efficacy and tolerability, as well as the dynamics of epileptiform activity index in adolescents and adults with newly diagnosed focal epilepsy during lacosamide therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…A number of studies have shown that the peculiarity of epilepsy in women is due to the hypothalamicpituitary-ovarian system with daily and monthly cycles, accompanied by diverse changes inherent only in the body of a woman: pregnancy, childbirth, lactation [2]. These and other studies show that women with epilepsy have a higher incidence of disorders such as menstrual irregularities, polycystic ovary syndrome, and infertility.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of studies have shown that the peculiarity of epilepsy in women is due to the hypothalamicpituitary-ovarian system with daily and monthly cycles, accompanied by diverse changes inherent only in the body of a woman: pregnancy, childbirth, lactation [2]. These and other studies show that women with epilepsy have a higher incidence of disorders such as menstrual irregularities, polycystic ovary syndrome, and infertility.…”
Section: Introductionmentioning
confidence: 96%
“…Epilepsy and pregnancy, management of pregnancy and childbirth remains a big problem for women with epilepsy. According to Russian researchers, over the past decades there has been a fourfold increase in the number of births among women with epilepsy [2,3]. In the world, 0.3% of newborns are born annually from women suffering from epilepsy [9,10].…”
Section: Introductionmentioning
confidence: 99%